Factors of Naming Efficiency - Olga V. Gosteva (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2017)
The article covers several factors of efficient commercial naming process. The linguistic study of proper names of businesses in Voronezh that we have conducted shows that such naming units are indirect speech acts with the intention of causing action. Their influence on an addressee is implicit. Such business names attain addressee persuasion by answering one of the following questions: "Who sells? What is sold? Whom is it sold?" The questions denote the three components of the commercial naming model that we have formulated. Any business name can be related to one of the components of the model. Efficiency of a business name depends on how clearly the author presents the selected component. Addressee factor is also important since the evaluation of a business name depends on the difficulty of its interpretation, character of associations (negative or positive) and the possibility of association with other business names. The article provides information about the proportions of the two types of business names, that is business names that reflect features of one particular business sphere and those that can be related to different spheres, depending on the type of business. The article also characterizes the possibility of using the same linguistic unit for naming businesses belonging to different types.